A compressive review on the effects of alcohols and nanoparticles as an oxygenated enhancer in compression ignition engine. (1st January 2020) - Nanthagopal, K.; Kishna, R. Susanth; Atabani, A.E.; Al-Muhtaseb, Ala'a H.; Kumar, Gopalakrishnan; Ashok, B.
Highlights: Impact of two oxygenated additives on diesel engine behaviours has been reviewed. Higher alcohols have shown better miscibility with diesel and biodiesel. Higher alcohols showed remarkable improvement in better combustion behaviours. Emulsified form of nanoparticles has improved the stability of blends. Zinc oxide nanoparticles seems to be a primary choice for better performance. Abstract: Ever since the research community highlighted the emission and sustainability aspects of pure diesel in the transportation sector, then began the search of next prospective fuel source that would address the shortcomings of diesel fuel. In the present review, a widespread assessment on the impact of two oxygenated additives on compression ignition engine characteristics has been discussed in detail. Alcohols composed of carbon atoms provide the edge to base fuel in terms of additional energy content and their cooling effect keeps the emissions in check. Nanoparticles, on the other hand, owe their impressive additive ability to their physical characteristics, providing larger surface area for the fuel reactivity and ability to atomize the base fuel. This review report summarizes the investigations carried out by the researchers on addition of various alcohols with diesel and biodiesel in different diesel engines. Various critical properties of each alcohols have been evaluated and their impact on compression ignition engine performance, combustion and emission characteristics have also been studies. In second phase of the review work, the importance of nanoparticle addition with diesel and biodiesel has been emphasised through their physical and chemical properties. Further review has been conducted on the effect of nanoparticles on all compression ignition engine behaviours when it has been doped with diesel and biodiesel at various concentrations. The review was suggested that all the higher alcohols like butanol and pentanol have better miscibility and stability compared to lower carbon content alcohols. Moreover, the lower cooling effect and autoigntion ability caused by higher alcohols would be primary choice for additive format with diesel fuel. Many nanoparticles addition with diesel has been analysed and it has been noted all the nanoparticles have shown better performance, combustion and emission behaviours. The zinc oxide and carbon nanotubes are the most preferable nano-particles compared to others due to their better anticorrosion behaviours and thermal conducting behaviours. Finally, it has been concluded that more extensive research works have to be done on the stability behaviour of alcohol and nanoparticles added diesel blends for their usage in commercial applications. The studies on the effect of nanoparticles addition with diesel or biodiesel on diesel engine life need to be done before its selection for long term applications.